Storia e contesto dell’egemonia dell’etica nel discorso pubblico - Donatelli, Piergiorgio (Filosofia Morale/Moral Philosophy, 2022)
The article explores some reasons that explain the crucial role played by ethics within public discourse at this stage of human history. Faced with the weakness of political discourse and the loss of religion’s power to shape public discourse, moral discourse has made its entrance, occupying the space left free by both of them. To understand its relevance, the article focuses in particular on bioethics, responsible for having brought to the center both the specificity of ethical analysis, in questions concerning, for example, the moral status of life and death, and the reflective, critical and revisionist dimension of ethics, which allows to shed light on the changes and challenges of contemporaneity, also indicating possible ways out and paradigm changes.